Design and Development of Battery Energy Storage System for Portable Electricity Supply - Anto, Budhi; Dahliyusmanto, Dahliyusmanto; Jahrizal, Jahrizal (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The demand for portable power sources has been on the rise, particularly for supplying electricity for mobile food vendors and smale-scale enterprises that operate during the night. With portable power sources, these merchants can sell freely in crowded areas without the concern of electricity availability for their cooking equipment and business lighting. This article present the design and development of a portable battery energy storage system (BESS) intended for use by mobile culinary businesses. A portable BESS comprises a battery pack, a power inverter, and a transfer switch, all integrated into a compact unit, along with a separate battery charger. The battery utilized is of the lithium-ferro-phosphate (LFP) type which provides benefits such as high energy density, lightweight design, and a long lifespan. The design process for the portable BESS begins with an estimation of the daily electricity demand of the electrical installation, then followed by determining the required storage capacity of the battery pack and the ratings for power inverter and transfer switch. The specifications for the BESS are 0.768kWh/220V/50Hz/1000W. Functional tests have been conducted, revealing that the BESS can be fully charged in 3 hours and can power five 19-W LED lights for up to 6.5 hours.